2011
DOI: 10.1161/hypertensionaha.110.160911
|View full text |Cite
|
Sign up to set email alerts
|

Role of Home Blood Pressure Monitoring in Overcoming Therapeutic Inertia and Improving Hypertension Control

Abstract: Abstract-Hypertension remains the most common modifiable cardiovascular risk factor, yet hypertension control rates remain dismal. Home blood pressure (BP) monitoring has the potential to improve hypertension control. The purpose of this review was to quantify both the magnitude and mechanisms of benefit of home BP monitoring on BP reduction. Using a structured review, studies were selected if they reported either changes in BP or percentage of participants achieving a pre-established BP goal between randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
339
1
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(364 citation statements)
references
References 39 publications
7
339
1
17
Order By: Relevance
“…2,23 A systematic review, followed by a recent meta-analysis, has shown that HBPM counters clinical inertia, leading the physician to more strictly seek the therapeutic goal, resulting in better BP control. 24 Another meta-analysis of 18 randomized, controlled trials observed that in hypertensive patients followed up at health units, the use of HBPM, compared with casual BP measurements, resulted in better BP control and higher likelihood of reaching adequate BP targets, strengthening the applicability of the method to the management of hypertension. 23 Prospective studies have shown that HBPM values were better correlated to cardiovascular and renal complications when compared to ambulatory measurements.…”
Section: Discussionmentioning
confidence: 99%
“…2,23 A systematic review, followed by a recent meta-analysis, has shown that HBPM counters clinical inertia, leading the physician to more strictly seek the therapeutic goal, resulting in better BP control. 24 Another meta-analysis of 18 randomized, controlled trials observed that in hypertensive patients followed up at health units, the use of HBPM, compared with casual BP measurements, resulted in better BP control and higher likelihood of reaching adequate BP targets, strengthening the applicability of the method to the management of hypertension. 23 Prospective studies have shown that HBPM values were better correlated to cardiovascular and renal complications when compared to ambulatory measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the difference may be due to increased adherence to drug treatment. We should point out that some studies have shown even better results when allowed and directed the patient to do self-adjustment on doses of drugs, according to SMBP 5,9 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypertensive patients accompanied with the SMBP have better blood pressure control compared to those followed by the casual measurement. This improvement is slight, but significant, and it can still be implemented in the use of methodologies that allow the self-adjustment of the medication by the patient, monitored remotely by health professionals 5,9 . It is interesting to notice that, even with a few measures, the SMBP has better predictive value for stroke (CVA) of the casual measurement, however, the greater the number of measures, the better the risk prediction 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number needed to treat to avoid one case of noncompliance was 5.6 patients. Moreover, a systematic review and meta-analysis that included 9446 participants randomised to home or clinic BP monitoring concluded that the former is associated with less therapeutic inertia [27]. The investigators additionally reported that compared with clinic BP measurement, both systolic and diastolic BP improved with home-based BP monitoring.…”
Section: Recommendationmentioning
confidence: 99%